Autoimmune Atrophic Gastritis: The Role of miRNA in Relation to Helicobacter Pylori Infection - Zingone, Fabiana; Pilotto, Valentina; Cardin, Romilda; Maddalo, Gemma; Orlando, Costanza; Fassan, Matteo; Marsilio, Ilaria; Collesei, Eugenio; Pelizzaro, Filippo; Farinati, Fabio (Frontiers in Immunology, 2022)
Introduction. MicroRNAs (miRNAs) have been proposed as diagnostic markers, biomarkers of neoplastic progression, and possible therapeutic targets in several immune-mediated diseases. We aimed to analyse the expression profile of selected miRNAs (miR21, miR142, miR223, miR155) in patients with autoimmune atrophic gastritis (AAG), patients with non-autoimmune multifocal atrophic gastritis (MAG), and healthy control subjects (HC). Materials and methods. A total of 103 patients with AAG were consecutively recruited for this study among those attending our gastroenterology outpatient clinic. Participating patients were subdivided into two groups: primary, not Helicobacter pylori (HP)-associated related AAG (n=57, P-AAG) and HP- associated related AAG (n=46, HP-AAG); this subgroup included HP-positive patients, patients with previously reported HP infection and patients harboring antral atrophy, considered as a stigma of HP infection. We also included 20 sex-age-matched MAG patients and 10 HC. Each AAG and MAG patient underwent upper GI endoscopy. Upper endoscopy with gastric biopsies was performed on each AAG and MAG patient. Circulating levels of miR21-5p, miR142-3p, miR223-3p, and miR155-5p were measured by RT-PCR in all groups. Results. MiR-21 was over-expressed in P-AAG (p=0.02), HP-AAG (p 0.04) and MAG (p=0.03) compared with HC. By contrast, miR-142 was more expressed in HC than in HP-AAG (p=0.04) and MAG (p=0.03). MiR-155 showed no significant differences among the four subgroups, while, unexpectedly, miR-223 was overexpressed in HC compared to P-AAG (p=0.01), HP-AAG (p=0.003), and MAG (p<0.001), and was higher in P-AAG than in MAG (p=0.05). Conclusions. MiR-21 was over-expressed in patients with gastric precancerous conditions irrespective of etiology, while in the same subgroups miR-142 and miR-223 were under-expressed compared to healthy controls. MiRNA levels did not discriminate P-AAG from HP-AAG and both from MAG but their circulating levels, when increased, identify patients at risk for gastric cancer. Controlling miRNAs up or downregulation could lead to a breakthrough in treating chronic autoimmune diseases and potentially interfere with progression to cancer.